Turkmenistan's strategy and policy regarding energy resources - Sabir Shukurov (Науковий вісник Мукачівського державного університету. Серія Економіка, 2022)
The relevance of the study is based, on the one hand, on the persisting importance and demand for minerals as energy carriers in the context of the global economy, and, on the other hand, on the recognition of the current economic processes taking place in the region of interest ( for this study, Central Asia) when building a strategy for the reintegration of the post-Soviet space. The purpose of the investigation is to characterise Turkmenistan’s current energy trade policy to anticipate further steps in building a system of strategic cooperation with its immediate neighbours as well as other political actors. The study uses general scientific methods and a range of special methods, such as deduction and induction methods, content analysis, event analysis, systematic approach and historical analysis. The study first outlines major developments in international politics (with a focus on past and current economic processes, specifically in trade and energy production) in the region as a whole and Turkmenistan in particular, and second, it proposes a scenario for the state’s likely development in the region of interest, based on historical assumptions and available data. The information set out in this study can be used to adjust actions in building a long-term relationship with Turkmenistan, and to assess and understand the motivations behind the actions of Turkmenistan’s officials